The Effect Of Motivation On The Performance Of Women Msme Actors In Purbalingga Regency Through Family Support As A Moderation Variable - Sinatria, Ridhwan; Osijo, Immanuel Ustradi; Sumunu, Trenggono; Soleha, Siti Nur; Zainuddin, Ahmad (Abadi Institute, 2025)
This study aims to analyze the influence of motivation on the performance of women Micro, Small, and Medium Enterprises (MSMEs) in Purbalingga Regency with family support as a moderation variable. A quantitative approach was used by distributing questionnaires to 150 respondents who were members of the Purbalingga Entrepreneur Muslim community. Data analysis was carried out using the Partial Least Square (PLS-SEM) method. The results of the study show that motivation has a positive and significant effect on the performance of women MSME actors. Family support has also been shown to have a positive and significant effect on performance, especially through emotional and practical aspects. However, family support is not significant in moderating the relationship between motivation and performance, which means internal motivation is a major factor driving performance improvement. These findings confirm that women's empowerment programs for MSME actors are more effective when they focus on strengthening individual motivation, while the role of the family functions as additional indirect support.